A multi-grain model for migration recrystallization in polar ice - Staroszczyk, R. (Archives of Mechanics, 2009)
In the paper a multi-grain model for a migration recrystallization phenomenon in polar ice is presented. A single crystal of ice is treated as a transversely isotropic and incompressible medium which deforms by viscous creep. The anisotropic viscous behaviour of the ice crystal is described by a constitutive law that includes three microscopic viscosity parameters, and the macroscopic behaviour of the polycrystal is derived by adopting the Taylor–Voigt approximation of the velocity gradient homogeneity in the material. It is assumed that recrystallize, that is gradually disappear, these crystals which are most stressed, and at their expense new crystals are nucleated with the orientations that enhance the deformation of the polycrystal. The model predictions are illustrated by results of numerical simulations of simple flows, showing the evolution of the oriented structure of ice and the variation of macroscopic viscosities with increasing strains.